Personality traits, individual innovativeness and satisfaction with life - Ali Imran (Journal of Innovation & Knowledge (JIK), 2019)
There is plenty of research on personality traits that explains its impact on human behaviors in different situations. However, there is sparse research available in the literature that explains how does personality traits affect innovativeness among individuals and satisfaction with life perceptions (subjective wellbeing). The current study proposes and empirically examines a conceptual model that addresses this important gap in the body of knowledge. Famous Big-Five personality traits theory is used to explain this phenomenon in this research. Data is collected from 613 students enrolled in different executive, master and PhD level programs in different universities of Pakistan. The study found positive influence of extraversion, agreeableness, conscientiousness, and openness to experience on individual innovativeness and satisfaction with life perceptions. Neuroticism is found to be negatively related to individual innovativeness and satisfaction with life perceptions. Finally, the study noted a positive association between individual innovativeness and perception with life. The applications and implications of this research are discussed in details.
Keywords: 650; Big-Five personality traits; Individual innovativeness; Satisfaction with life